An efficient synthesis of novel bioactive azetidinones and thiazolidinones of 1, 5-dimethyl-2-phenyl-1h-pyrazol-3(2h)-one - JYOTSNA S. MESHRAM; HIMANI N. CHOPDE; RAMAKANTH PAGADALA; VENKATESHWARLU JETTI (International Journal of Pharma and Bio Sciences, 2011)
A novel series of azetidinones, 3-chloro-4-(2-hydroxyphenyl)-1-(4-(4-(arylphenyl)2,3,5,6-tetramethyl-1,7-diphenyl-1,2,7,7a-tetrahydrodipyrazolo[3,4-b:4’,3’-e ]pyridin-8 (4H, 6H, 8a H)-yl)phenyl)azetidin-2-one (3a-3e) and thaizolidinones; 2-(aryl phenyl)-3-(4-(4-(2hydroxyphenyl)-2,3,5,6-tetramethyl-1,7-diphenyl-1,2,7,7a-tetrahydro-dipyrazol o[3,4-b:4’,3’e]pyridin-8(4H,6H,8a H)yl)phenyl) thiazolidin-4-one (4a-4e) were synthesized using new Schiff bases, 2-(8-(4-(arylbenzylideneamino)phenyl)-2,3,5,6-tetramethyl-1,7-diphen -yl1,2,4,6,7,7a,8,8a-octahydrodipyrazolo[3,4-b:4’,3’-e] pyridin-4-yl)phenol(2) (2a-2e). The Schiff bases were synthesized by the reaction of aromatic aldehydes, and 2-(8-(4-aminophenyl)2,3,5,6-tetramethyl-1,7-diphenyl-1,2,4,6,7, 7a, 8, 8a-octahydrodipyrazolo[3,4-b:4’,3’-e]pyridin4-yl)phenol (1) under microwave and conventional methods. Our results shows that the synthesis of Schiff base under solvent free microwave condition is the most efficient method of synthesis having highest yield than both conventional method and microwave with solvent. The newly synthesized compounds were characterized on the basis of different spectroscopic (IR, 1H-NMR, Mass) and elemental (CHN) analysis techniques. Compounds (3a-3e and 4a4e) were screened for their biological activities against the panel of nine bacterial strains.